Artesunate-loaded Fe3O4 nanoparticles: A novel approach for combating 4T1 breast cancer cells in vitro and in vivo - Amirreza Safdarian; Massoumeh Ebtekar; zouhair Mohammad Hassan; Hossein Naderi Manesh; Hashemi Seyed Ali; Saeed Samaeinasab; Danial Habibi; Hossein Khorramdelazad (Nanomedicine Journal)
Objective(s): Breast cancer is one of the most common cancers among women, and current treatments are inadequate due to unwarranted side effects and lack of specificity resulting in off target consequences. Artesunate is a synthetic anti-malarial drug that exerts inhibitory effects on cancer cell lines via apoptosis and has been used treating some cancers. This study investigated the anticancer effects of Fe3O4 magnetic nanoparticles conjugated with chitosan, polyethylene glycol, folic acid, and artesunate in vivo and in vitro.Materials and Methods: Nanoparticles were synthesized by co-precipitation; morphology and size were determined by scanning electron microscopy (SEM), and the presence of the components was verified by nanoscale Fourier transform infrared spectroscopy (FTIR).  4T1 murine mammary tumor cells were treated with nanoparticles, and cell viability was determined by MTT assay. 4T1 cells were also subcutaneously injected into BALB/c mice, and magnetic resonance imaging was carried out two weeks later to determine tumor size among the groups.  Interferon gamma (IFN-γ) and IL-4 levels (in splenocytes culture supernatant) were measured by ELISA, and tumors, surrounding tissues, and mouse livers were histopathologically studied. Results: The nanoparticle made in this article had good anticancer effects and caused apoptosis in cancer cells in breast cancer, and also strengthened the cellular immune system and further increased interferon gamma and increased the half-life of mice with cancer, while this nanoparticle It did not have the side effects of chemotherapy drugs.Conclusion: Artesunate-containing nanoparticles decreased 4T1 cell viability and increased apoptosis to a greater extent than nanoparticles without the drug. In vivo, artesunate nanoparticles showed no toxicity and were more effective in decreasing tumor size than control. They were also associated with increased survival, increased IFN-γ, and decreased IL-4 levels in the spleen. The findings show the drug targets cancer  cells effectively with minimal side effects due to its herbal nature and targeted nano delivery.